PV cools: Close loop water cooling system for PV module - Firdaus, Basrawi; Chandran, Puganesa (2021)
Significant drop in performance due to extreme rise in solar cells temperature. Dust deposition on the module surface inhibits the incoming solar irradiation from reaching the solar cell.